Drug-resistant tuberculosis: integrative review of nursing care in primary health care - Sibele Naiara Ferreira Germano; Alacoque Lorenzini Erdmann; Camila Freire Albuquerque; Lúcia Nazareth Amante; Darlisom Sousa Ferreira; Marlucia da Silva Garrido (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to identify, in the scientific literature, the care that should be provided to individuals with drug-resistant tuberculosis by nurses in primary health care. Methods: integrative review, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses study selection flowchart. Data collection was conducted in November 2022, across ten databases. Results: six studies emphasized that nurses should perform directly observed treatment; two highlighted the importance of integrated care management between tuberculosis and human immunodeficiency virus; two demonstrated comprehensive nursing consultation using the nursing process; one emphasized person-centered care, with discharge planning and improved hospital communication with primary health care services. Final Considerations: the care that nurses should provide to individuals with drug-resistant tuberculosis in primary health care, for care resolution, is evidence-based.